Effects of varus orthotics on lower extremity kinematics during the pedal cycle - Sinclair, J.; Vincent, H.; Taylor, P. J.; Hebron, J.; Hurst, H. T.; Atkins, S. (Human Movement, 2014)
Cycling has been shown to be associated with a high incidence of chronic pathologies. Foot orthoses are frequently used by cyclists in order to reduce the incidence of chronic injuries. The aim of the current investigation was to examine the influence of different varus orthotic inclines on the three-dimensional kinematics of the lower extremities during the pedal cycle. Methods. Kinematic information was obtained from ten male cyclists using an eight-camera optoelectronic 3-D motion capture system operating at 250 Hz. Participants cycled with and without orthotic intervention at three different cadences (70, 90 and 110 RPM). The orthotic device was adjustable and four different wedge conditions (0 mm - no orthotic, 1.5 mm, 3.0 mm and 4.5 mm) were examined. Two-way repeated measures ANOVAs were used to compare the kinematic parameters obtained as a function of orthotic inclination and cadence. Participants were also asked to subjectively rate their comfort in cycling using each of the four orthotic devices on a 10-point Likert scale. Results. The kinematic analysis indicated that the orthotic device had no significant influence at any of the three cadences. Analysis of subjective preferences showed a clear preference for the 0 mm, no orthotic, condition. Conclusions. This study suggests that foot orthoses do not provide any protection from skeletal malalignment issues associated with the aetiology of chronic cycling injuries.